2009
DOI: 10.1007/s10803-009-0736-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Symptom Domains in Autism Spectrum Disorders: A Population Based Twin Study

Abstract: Factor structure and relationship between core features of autism (social impairments, communication difficulties, and restricted, repetitive behaviours or interests (RRBIs)) were explored in 189 children from the Twins Early Development Study, diagnosed with autistic spectrum disorders (ASDs) using the Development and Wellbeing Assessment (DAWBA; Goodman et al. in J Child Psychol Psyc 41:645-655, 2000). A bottom-up approach (analysis 1) used principal component factor analysis of DAWBA items indicating five f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
42
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 39 publications
6
42
1
1
Order By: Relevance
“…Previous results (9)(10)(11)30) and the present study concur in suggesting that there are a degree of overlapping genetic and environmental influences between different autism behaviors in the general population but also significant genetic and environmental influences that are specific to each part of the autism triad. One slight difference is that while the results from the UK twin studies found that SIs and RRBIs showed the least amount of phenotypic and genetic overlap within the triad, the present study found that this overlap was highest between SIs and RRBIs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous results (9)(10)(11)30) and the present study concur in suggesting that there are a degree of overlapping genetic and environmental influences between different autism behaviors in the general population but also significant genetic and environmental influences that are specific to each part of the autism triad. One slight difference is that while the results from the UK twin studies found that SIs and RRBIs showed the least amount of phenotypic and genetic overlap within the triad, the present study found that this overlap was highest between SIs and RRBIs.…”
Section: Discussionsupporting
confidence: 90%
“…These previous twin studies have reported modest to moderate genetic overlap across different parts of the autistic triad in the general population (9), in extremescoring groups (10), and in children with suspected ASDs based on a parent interview (11,12). These findings suggest that while some genetic influences may confer risk for developing all the symptoms of the autistic triad, others are specific to particular symptoms.…”
mentioning
confidence: 78%
“…However, Wing and Gould (1979) themselves noted that some children presented with only certain aspects of the triad. More recently, it has been found that 10% of children in the general population present with just one impairment (defined as scoring in the most impaired 5%) without co-occurring deficits in other parts of the triad (Ronald et al, 2006a), and modest-to-low phenotypic correlations between triad features have been reported in individuals with ASD (Dworzynski et al, 2009) and trait-wise in general population samples (Ronald et al, 2006b). These findings have been taken to suggest that the triad of impairments is separable at the behavioural level, although this has been a matter of some debate.…”
Section: Introductionmentioning
confidence: 99%
“…O autismo pode ser considerado uma síndrome comportamental com etiologias múltiplas podendo haver disfunções neurobiológicas, genéticas e déficits psicológicos como base para os déficits cognitivos encontrados nesta patologia (Gillberg, 1990, Baron-Cohen & Bolton, 1993Batley, Phillips e Rutter, 1996;Towbin, 1997, Rutter, 2005, Dworzynski, Happé, Bolton, & Ronald, 2009, David & cols., 2010, Spek, Scholte, & van Berckelaer-Onnes, 2010.…”
unclassified